The Health Behavior Model of Personality in the Context of a Public Health Crisis. Issue 4 (20th May 2021) - Willroth, Emily C.; Smith, Angela M.; Shallcross, Amanda J.; Graham, Eileen K.; Mroczek, Daniel K.; Ford, Brett Q.
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: The US Centers for Disease Control and Prevention recommended behavioral measures to slow the spread of COVID-19, such as social distancing and wearing masks. Although many individuals comply with these recommendations, compliance has been far from universal. Identifying predictors of compliance is crucial for improving health behavior messaging and thereby reducing disease spread and fatalities. Methods: We report preregistered analyses from a longitudinal study that investigated personality predictors of compliance with behavioral recommendations in diverse US adults across five waves from March to August 2020 ( n = 596) and cross-sectionally in August 2020 ( n = 405). Results: Agreeableness—characterized by compassion—was the most consistent predictor of compliance, above and beyond other traits, and sociodemographic predictors (sample A, β = 0.25; sample B, β = 0.12). The effect of agreeableness was robust across two diverse samples and sensitivity analyses. In addition, openness, conscientiousness, and extraversion were also associated with greater compliance, but effects were less consistent across sensitivity analyses and were smaller in sample A. Conclusions: Individuals who are less agreeable are at higher risk for noncompliance with behavioral mandates, suggesting that health messaging can be meaningfully improved with approaches that address these individuals in particular. These findings highlight the strong theoretical and practical utility of testing long-standing psychological theories during real-world crises.